Characterisation and optimisation of MEMS based pressure sensors for deep space missions. (4th December 2019) - Narayan, R.; Sidhick, Aisha; Shekar, GL; Prasad, MVN
Abstract: Pressure sensors are extensively used in spacecraft propulsion system for health monitoring and determining the on‐orbit functional life of the spacecrafts. This is possible by employing PVT (Pressure‐Volume‐Temperature) method wherein pressure sensors and temperature sensors mounted in the propellant tank are used for accurate measurement of pressure and temperature. Pressure sensors are also employed for control & other system health monitoring applications. For aerospace applications, they have to perform under harsh and volatile environments and demands utmost reliability and long‐term performance stability. Hence, it is essential to characterise and optimise these sensors by adopting adequate design methodologies test philosophies. A detailed study has been carried out and the performances were evaluated for establishing the usage of MEMS based pressure sensors.